Effectiveness of an Education Program on Nurses’ Practices toward Some Sterilization Techniques at Emergency Department in Al-Diwaniya Teaching Hospital - Wissam Mohammed Kareem; Sabah Abbas Ahmed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Sterilization procedures is an essential clinical competency in health care to minimize visibility of hospital staff, guests, patients, and their visitors, follow both of these grooming instructions. incorporate infectious control and outbreak detection techniques across all healthcare systems Since one of the main factors for medical services is the prevention of infectious infections, the health care team must consider infection management and infection control as well. in order to deter the transmission of microorganisms, process involves all hands-use, safety clothing (gowns, masks), and adequate waste disposal.the aim of this research is to evaluate nursing’s sterilization techniques. The preliminary pre-experimental architecture was put in place in place in Al-Dani Teaching Hospital for the duration of the timeframe from (17 September, 2020 to 16 March, 2021) on non-probability sampling of 30 Emergency department staff.The analysis showed major changes in the application of sterile domains from before the evaluation (pvalue=0.0001). The researcher found that emergency department nurses did not use appropriate sterilization techniques prior to the introduction of an instructional curriculum, yet after the application, they demonstrated high quality toward the use of sterilization techniques Facilities and medical equipment are urged to develop their awareness and sterilization procedures in the ED; it also, emergency nurses with additional experience are invited to join